Estimation of genetic diversity and identification of potential rice lines for two-line hybrid based on microsatellite marker and phenotypic trait analyses - Nur Azreen, M.; Siju, S.; Bhuiyan, M.A.R.; Wickneswari, R. (Penerbit Universiti Kebangsaan Malaysia, 2014)
The genetic relatedness among 31 advanced breeding lines derived from crosses between O. rufipogon and MR219, three Malaysian rice varieties (MR219, MR253 and MR263) and two thermosensitive genic male sterile (TGMS) lines (IR73827- 23-26-15-7S and IR77271–42–5–4–36S) were determined using different microsatellite (SSR) markers. A total of 81 alleles were detected with the 26 SSR markers, with an average of 3.12 alleles per locus and a PIC value varying from 0.028 to 0.450. UPGMA cluster analysis separated the entire accessions into seven major groups. Group I accommodated twenty two advanced breeding lines along with the parental variety, MR219. Eight advanced breeding lines formed the Group III while Group II, IV, V, VI and VII contained either a single improved line or variety. Group II was constituted by the improved line G33, while Group IV and V were constituted by the released varieties MR253 and MR263, respectively. On the other hand, two TGMS lines viz. IR73827-23-26-15-7S and IR77271–42–5–4–36S were clustered under Group VI and Group VII, respectively. Based on the genetic distance (GD) data derived from the analysis, three combinations with maximum GD viz., MR253 x G33 (GD= 0.61), MR253 x G02 (GD= 0.61) and MR253 x G16 (GD=0.56) are suggested to be used as parental lines in two line hybrid rice breeding system. Besides GD, the suggested lines possess promising yield and yield related traits. The released variety, MR253 is suggested to be developed as a TGMS line. These suggested parental lines are expected to produce highest hybrid vigour and will be useful for future breeding programmes.